Do Accounting Information Systems, Internal Control, IT Utilization, and HR Competence affect Financial Reports Quality? - Widiasalwa, Syadzwana; Asaari, Masagus; Zhafiraah, Nazma Riska (Research of Accounting and Governance, 2024)
The purpose of internal research is to determine the effects that information technology (IT) use, internal control systems, accounting information systems, and human resource (HR) competencies have on PT. Akebono Brake Astra Indonesia's financial statements. 38 respondents filled out questionnaires as part of the study's research methodology. In this study, the types of data quality assessments used were validity and reliability tests. The conventional assumption tests that were used in this study were the multicollinearity, heteroscedasticity, and normality tests. The variables pertaining to the accounting information system and the use of information technology, on the other hand, have a positive and significant impact, according to the results of the multiple linear regression test, coefficient of determination test, t-test, and F-test that were used in this study. on the caliber of bank accounts. The efficacy of the internal control system and human resources are unaffected in the interim by the accuracy of the financial statements. Its management implications include enhanced operational efficiency, data quality and reliability, and information technology utilization optimization.